Developmental aspects of cortical excitability and inhibition in depressed and healthy youth: an exploratory study - Croarkin, Paul E.; Nakonezny, Paul A.; Lewis, Charles P.; Zaccariello, Michael J.; Huxsahl, John E.; Husain, Mustafa M.; Kennard, Betsy D.; Emslie, Graham J.; Daskalakis, Zafiris J. (Frontiers in Human Neuroscience, 2014)
Abstract Objectives: The objective of this post hoc exploratory analysis was to examine the relationship between age and measures of cortical excitability and inhibition. Methods: Forty-six participants (24 with major depressive disorder and 22 healthy controls) completed MT, SICI, ICF, and CSP testing in a cross-sectional protocol. Of these 46 participants, 33 completed LICI testing. Multiple linear robust regression and Spearman partial correlation coefficient were used to examine the relationship between age and the TMS measures. Results: In the overall sample of 46 participants, age had a significant negative relationship with motor threshold in both the right (rs = -0.49, adjusted p = .007; β= -0.08, adjusted p=.001) and left (rs = -0.42, adjusted p = .029; β= -0.05, adjusted p=.004) hemispheres. This significant negative relationship of age with motor threshold was also observed in the sample of depressed youth in both the right (rs = -0.70, adjusted p = .002; β= -0.09, adjusted p=.001) and left (rs = -0.54, adjusted p = .034; β= -0.05, adjusted p=.017) hemispheres, but not in healthy controls. In the sample of the 33 participants who completed LICI testing, age had a significant negative relationship with LICI (200 millisecond interval) in both the right (rs = -0.48, adjusted p = .05; β= -0.24, adjusted p=.007) and left (rs = -0.64, adjusted p = .002; β= -0.23, adjusted p=.001) hemispheres. This negative relationship between age and LICI (200 millisecond interval) was also observed in depressed youth in both the right (rs = -0.76, adjusted p = .034; β= -0.35, adjusted p=.004) and left (rs = -0.92, adjusted p = .002; β= -0.25, adjusted p=.001) hemispheres. Conclusion: These findings suggest that younger children have higher motor thresholds. This is more pronounced in depressed youth than healthy controls. LICI inhibition may also increase with age in youth.